THE INFLUENCE OF DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY (C SR ) ON COMPANY VALUE WITH INVESTOR’S ATTENTION AS INTERVENING VARIABLE (Empirical Study on Infrastructure Companies Listed on the Indonesia Stock Exchange 2018 - 2020) - Yuliartanti, Adelia Rahma; Handayani, Rr Sri (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosureon firm value with investor’s attention as an intervening variable in infrastructure sectorcompanies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The value of the company in this study is calculated by the company’s stock return. With more information provided by the company, it will attract investors’ attention and will reduce information asymmetry. The population in this study was taken from companies listed on the Indonesia Stock Exchange (IDX) in the Infrastructure sector in 2018-2020. Sampling was taken using purposive judgment sampling method which finally found 18 of the 71 companies listed on the IDX website. The analytical tool used is partial regression analysis (Partial Least Square/PLS). Resulting that social Corporate Social Responsibility (CSR) disclosure has a positive and significant influence on the value of the company while the disclosure of Corporate Social Responsibility (CSR) economy and environment has a negative effect on the value of the company, and the disclosure of corporate social responsibility (CSR) economically, socially and environmentally has a negative effect on the value of the company with investor’s attention as an intervening variable.